Dynamic Polyphosphazene Networks with Modulating Shape Memory and Self‐Healing Capacity by Double Coordination Interactions. Issue 10 (5th August 2021) - Wu, Zhaolin; Zhao, Yuanxi; Zhang, Liqun; Wang, Xiufen
Abstract: A modern class of self‐healing polyphosphazene elastomers has been synthesized using coordination bonds for the first time. Two categories of carboxyl‐modified polyphosphazene have been synthesized, and 16 cross‐linked polymers have been fabricated by tuning the concentration of different metal ions, which also allows modifying the properties of the elastomer by adjusting the interactions. This design enables the polymer network to form a hierarchical and dynamic structure without introducing complex ligands. The polyphosphazene networks can be toughened and enhanced by the dynamic coordination structure. Due to the distinct design, the synthesized elastomers show unprecedented properties in halogen‐free polyphosphazenes, including high tensile stress (1.82 MPa), high malleability (≈1100%), shape memory, self‐healing, and thermal processing capacity. Abstract : In this work, an ingenious strategy is offered to prepare self‐healing polyphosphazenes elastomers with two kinds of coordination bonds. Double coordination behavior occurs on the main chain and side group of polyphosphazenes, respectively, and simultaneously. This model affords the potential to obtain high‐performance elastomers by polyphosphazenes' intrinsic coordination behavior.